literature review THE ROLE OF THE DRIVING TEACHER IN THE FREE CURRICULUM OF THE FREE ERA OF LEARNING: THE ROLE OF THE DRIVING TEACHER IN THE FREE CURRICULUM OF THE FREE ERA OF LEARNING - Patiung, Amos; Lasmawan, I Wayan; Suharta, I Gusti Putu (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2024)
This research aims to explore the role of mobilizing teachers in the implementation of Merdeka Curriculum in Indonesia. The research method used is a literature review, in which various journal articles, books and related documents from several periods are systematically analyzed. The results show that the role of the driving teacher has a significant impact on the transformation of education towards the Merdeka Curriculum. The driving teacher not only acts as a teacher, but also as a learning facilitator who encourages students to be active, critical, and independent in the learning process. They also play a role in creating a learning environment that is inclusive, student-centered, and relevant to individual needs. In addition, teacher advocates also play an important role in integrating relevant learning technologies and media to enhance learning effectiveness. Adequate digital skills are key in optimally utilizing technological resources. This research also highlights the importance of the role of mobilizing teachers in realizing the vision of Merdeka Curriculum which is more inclusive, responsive, and relevant to students' needs. In conclusion, developing the role of mobilizing teachers is key in improving the quality of education and preparing future generations to face the challenges.